Rejuvenating ACP smallscale fisheries using ICTs - Mallalieu, Kim I. (Technical Centre for Agricultural and Rural Cooperation, 2015)
As the basis for rejuvenating small-scale fisheries in ACP countries, this report maps the pathway from fisher to the system of policy, legislation and practice that constrain his operation. The report reviews the existing use of ICTs in the small-scale fisheries value chain in ACP countries and finds that there is no strategic or operational framework within which these technologies are applied. Recommendations and cautions are offered to rejuvenate the small-scale fisheries sector within the context of its complex interdependencies and rich ecosystem.